Message - El-Zahaby, Dr. Sally A. (Universal Journal of Pharmaceutical Research, 2022)
Activeness and dedication of the all editors, is the main reason for the continuous success of this prestigious journal. I encourage all the Editors to collaborate together in multidisciplinary scientific researches especially to combat the recent pandemic of COVID-19. We can do it. The editors originated from different countries and they all have different scientific backgrounds so we can share the experience and contribute in publishing good articles. As far as my specialization is concerned I am expert in the field of nano-carriers as drug delivery systems with more than 10 years’ experience. Additionally, I have good experience in tablet dosage form enabling me to solve tablet manufacturing problems based on my publications concerning different types of tablets formulations including; effervescent mini-tablets, size expanding tablets and various types of osmotic tablets. So let’s start and work on a target of getting a good impact factor for our “UJPR”.